Cities, settlements and key infrastructure - DODMAN, David (Institutional Knowledge at Singapore Management University, 2022)
In all cities and urban areas, the risk faced by people and assets from hazards associated with climate change has increased (high confidence1 ). Urban areas are now home to 4.2 billion people, the majority of the world’s population. Urbanisation processes generate vulnerability and exposure which combine with climate change hazards to drive urban risk and impacts (high confidence). Globally, the most rapid growth in urban vulnerability and exposure has been in cities and settlements where adaptive capacity is limited, especially in unplanned and informal settlements in low- and middle-income nations and in smaller and medium-sized urban centres (high confidence). Between 2015 and 2020, urban populations globally grew by more than 397 million people, with more than 90% of this growth taking place in less developed regions.